(untitled) (Elmergib Journal of Human Sciences, 2025)
This research came under the title: The methods of wrongful parentation and their relationship to aggressive behavior among adolescents, and through research in the various methods that parents follow with their children, as they are diverse and different from one family to another, the methods have varied in terms of rejection and acceptance to tolerance of independence, neglecting exaggeration in care. The focus has been on methods (neglect, domination and excessive protection) and its relationship to aggressive behavior in adolescents. This research aims to reveal the relationship between the methods of the wrong parental treatment with aggressive behavior as the children realize, and the researchers used the descriptive analytical approach due to its suitability for this research. Information and data were collected through the questionnaire of (63) phrases distributed over four dimensions, namely (physical aggression, verbal aggression, anger, enmity). In this study, the researchers have adopted the application of methodological and scientific research tools to try to ensure the validity of the content or content of questions, using several technologies in addition to observation and interview. The research concluded that there is a statistically significant relationship (directly)Between the method of cruelty as a method of parental treatment and aggressive behavior of the teenager. And that there is a positive statistical relationship between the method of neglect and aggressive behavior of the teenager.